Factors predicting outcome after salvage treatment for stage IV oral squamous cell carcinoma: Evidence of the potential importance of the cyclooxygenase‐2–prostaglandin E2 pathway. Issue 8 (15th November 2014) - Kekatpure, Vikram D.; Singh, Mandeep; Selvam, Sumithra; Shetkar, Girish; Hedne, Naveen C.; Trivedi, Nirav P.; Siddappa, Gangotri; Govindan, Sindhu V.; Suresh, Amritha; Rangarajan, Bharath; Dannenberg, Andrew J.; Kuriakose, Moni Abraham.
Abstract Background We determined the clinicopathological factors that predicted outcome after salvage treatment for stage IV oral squamous cell carcinoma (OSCC). Additionally, the prognostic significance of the cyclooxygenase‐2 (COX‐2)/microsomal prostaglandin‐E synthase‐1 (mPGES‐1) pathway was evaluated. Methods Thirty‐one patients who underwent salvage surgery were included. COX‐2 and mPGES‐1 levels were quantified by real time polymerase chain reaction (PCR). Results The 2‐year disease‐free and overall survival rates were 46% and 53%, respectively. Adequacy of initial treatment, tobacco smoking, and the presence of pathological risk factors were predictive of mortality. In patients who had not received chemotherapy before salvage surgery, high levels of intratumoral COX‐2 and mPGES‐1 were associated with poor prognosis. By contrast, high intratumoral COX‐2 and mPGES‐1 after chemotherapy were associated with improved outcomes. Conclusion Clinicopathological factors may inform treatment decisions in patients with stage IV OSCC. Expression patterns of COX‐2 and mPGES‐1 correlated with outcome and warrant further investigation. © 2014 Wiley Periodicals, Inc. Head Neck37: 1142–1149, 2015